Visualization of Actin Polymerization in Invasive Structures of Macrophages and Carcinoma Cells Using Photoconvertible β-Actin – Dendra2 Fusion Proteins - Dovas, Athanassios (Public Library of Science, 2011)
Actin polymerization controls a range of cellular processes, from intracellular trafficking to cell motility and invasion. Generation and elongation of free barbed ends defines the regions of actively polymerizing actin in cells and, consequently, is of importance in the understanding of the mechanisms through which actin dynamics are regulated. Herein we present a method that does not involve cell permeabilization and provides direct visualization of growing barbed ends using photoswitchable β-actin - Dendra2 constructs expressed in murine macrophage and rat mammary adenocarcinoma cell lines. The method exploits the ability of photoconverted (red) G-actin species to become incorporated into pre-existing (green) actin filaments, visualized in two distinct wavelengths using TIRF microscopy. In growing actin filaments, photoconverted (red) monomers are added to the barbed end while only green monomers are recycled from the pointed end. We demonstrate that incorporation of actin into intact podosomes of macrophages occurs constitutively and is amenable to inhibition by cytochalasin D indicating barbed end incorporation. Additionally, actin polymerization does not occur in quiescent invadopodial precursors of carcinoma cells suggesting that the filaments are capped and following epidermal growth factor stimulation actin incorporation occurs in a single but extended peak. Finally, we show that Dendra2 fused to either the N- or the C-terminus of β-actin profoundly affects its localization and incorporation in distinct F-actin structures in carcinoma cells, thus influencing the ability of monomers to be photoconverted. These data support the use of photoswitchable actin-Dendra2 constructs as powerful tools in the visualization of free barbed ends in living cells.